RETINOPATHY RISK FACTORS AMONG DIABETICS IN A TERTIARY CARE MILITARY HOSPITAL - Ameen, Sameer Shahid; Niazi, Muhammad Khizar; Saeed, Kamran; Yaqub, Muhammad Amer; Khan, Muhammad Dawood (Pakistan Armed Forces Medical Journal, 2011)
Objective: To determine the frequency and risk factors for severity of retinopathy in diabetic patients referred to a tertiary military hospital. Study Design: Cross-sectional study. Place and duration of study: Armed Forces Institute of Ophthalmology, Rawalpindi from Jun 2008 to Dec 2009. Patients and Methods: Diabetic patients aged 40 to 79, referred for suspected diabetic retinopathy (DR) on fundoscopy from medical outpatient clinic of Military Hospital Rawalpindi were randomly included in the study. Participants underwent a standardized interview and examination. Retinopathy was assessed through dilated pupils, and graded into absent retinopathy, mild to moderate, or advanced. Presence of clinically significant macular edema (CSME) was also recorded. To evaluate the simultaneous effect of significant risk factors on the different stages of DR, multivariate regression analysis was carried out. Results: Out of five hundred and ten patients, DR was confirmed in 63% cases with advanced retinopathy in 21.3%. In univariate analysis, duration of diabetes, fasting blood glucose, and presence of macular oedema were significantly associated with retinopathy (P<0.005). On multivariate analysis, however, only duration of diabetes (Odds Ratio 6.15 for 5 to 10 years and 38.29 for more than 10 years) and macular oedema (OR 6.617 95% CI 3.95-11.07) remained significant. CSME was present in 173 (33%) patients and its frequency increased with the severity of DR (P <0.001). Conclusion: The frequency of DR among military personnel and their dependants was high with strong association to duration of diabetes. This underscores the importance of regular retinal examination to detect DR in the early stages and timely intervention to prevent diabetes related blindness.